Inhibiting Factors for Poverty Reduction and Alleviation Strategies: Interpretative Structural Modeling Approach - Fafurida; Prajanti, Sucihatiningsih Dian Wisika; Shanty Oktavilia (JEJAK, 2025)
This research aims at analyzing Inhabiting Factors for the Success of Poverty Handling and Its Alleviation Strategy in Kebumen Regency. This research uses two types of data sources, primary and secondary data. The population in this research is the poor people in Kebumen Regency. The research takes the proportional random sampling technique. This technique is used because of the grouping of the poor in Kebumen Regency. There are 100 poor people as the samples in Kebumen Regency. The first analysis method in this research, which is the analysis of inhibiting factors for poverty alleviation in Kebumen Regency, is the Interpretative Structural Modeling (ISM) analysis. The second is the Mactor method. The third one is the Analytical Hierarchy Process (AHP), which is a comprehensive decision-making model that takes into account qualitative and quantitative matters. The results of research indicate that poverty alleviation efforts in Kebumen Regency require the involvement of various parties, either from the government, academics, the community, entrepreneurs, the media and also NGOs. The results of analysis indicate that there are eight actors who play key roles in poverty alleviation in Kebumen Regency, including the Kebumen Regency Government, Universities and Educational Institutions, Business Actors and Industries, international organizations and donors, Non-Governmental Organizations, Mass Media, Religious Organizations and also Local Communities. The most prioritized policies in poverty alleviation efforts in Kebumen Regency are as follows. The first is improving education and skills. The second priority is health services. The third one is improving basic infrastructure. While the last priority is local economic empowerment.